The Relationship between Sleep Complaints, Depression, and Executive Functions on Older Adults - Almondes, Katie M. de; Costa, Mônica V.; Malloy-Diniz, Leandro F.; Diniz, Breno S. (Frontiers in Psychology, 2016)
Aim: In this manuscript, we report data on the association between executive functions screened by Frontal Assessment Battery, Five Digit Test and Digit Span with self-reported depressive symptoms and sleep complaints in nondemented older adults. Methods: A total sample of 95 nondemented older adults performed Geriatric Depression Scale short version, Frontal Assessment Battery, Five Digit Test, Digit Span and clinical interview. We split participants in groups stratified by age according to: young-old (60-69 years of age), old-old (70-79 years) and oldest-old (> 80 years) and compared these three groups on the sociodemographic characteristics and executive functions performance. We carried out Poisson regression with robust error variance to verify sleep complaints and depression effects on executive functions performance. Gender, age, years of formal education, use of antidepressants and of benzodiazepines were considered as confounding variables, taking into account executive functions as dependent and sleep complaints and depression as independent variables. Results: Controlling the effect of age, gender, years of formal education, use of benzodiazepines and of antidepressants there was a significant influence of depression in motor programming, inhibitory control and working memory. Individuals without depression show motor programming scores 68,4% higher, inhibitory control scores 3 times greater and working memory scores also 3 times greater than individuals without depression. There was a significant influence of sleep complaints in phonemic fluency, motor programming, inhibitory control and working memory. Individuals without sleep complaints show phonemic fluency scores 2 times greater than, motor programming scores 85,9% higher, inhibitory control scores 3 times greater and working memory scores also 3 times greater than individuals without sleep complaints. Conclusions: Sleep complaints are associated with phonemic fluency, motor programming, inhibitory control and working memory impairment. Depression symptoms presence are associated with motor programming and working memory performances. Depression and sleep complaints interaction would determine worse phonemic fluency, inhibitory control and working memory cognitive performance than these two conditions alone.